2023
DOI: 10.1111/jcmm.18001
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐type‐specific gene expression and regulation in the cerebral cortex and kidney of atypical Setbp1S858R Schinzel Giedion Syndrome mice

Jordan H. Whitlock,
Tabea M. Soelter,
Timothy C. Howton
et al.

Abstract: Schinzel Giedion Syndrome (SGS) is an ultra‐rare autosomal dominant Mendelian disease presenting with abnormalities spanning multiple organ systems. The most notable phenotypes involve severe developmental delay, progressive brain atrophy, and drug‐resistant seizures. SGS is caused by spontaneous variants in SETBP1, which encodes for the epigenetic hub SETBP1 transcription factor (TF). SETBP1 variants causing classical SGS cluster at the degron, disrupting SETBP1 protein degradation and resulting in toxic accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Further, we examined the gene expression of 209 known SETBP1 targets we previously compiled [ 11 ] from SETBP1 ChIP-seq binding sites [ 28 ], MSigDB [ 29 ], SIGNOR [ 30 ], TRRUST [ 31 ], Piazza et al [ 2 ], and Antonyan et al [ 10 ]. We found that most known SETBP1 targets were also broadly expressed across adult human tissues (62.2% of known SETBP1 targets had a TPM>3 in >90% of tissues; Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, we examined the gene expression of 209 known SETBP1 targets we previously compiled [ 11 ] from SETBP1 ChIP-seq binding sites [ 28 ], MSigDB [ 29 ], SIGNOR [ 30 ], TRRUST [ 31 ], Piazza et al [ 2 ], and Antonyan et al [ 10 ]. We found that most known SETBP1 targets were also broadly expressed across adult human tissues (62.2% of known SETBP1 targets had a TPM>3 in >90% of tissues; Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, prior research showed that oncogenic apoptosis resistance and unresolved DNA damage signatures persist due to SETBP1 variants in SGS [ 11 , 37 ]. Here, we found that in non-diseased adult tissue, TCF4, a known apoptosis regulator [ 38 , 39 ], and APEX1, part of the SET complex in DNA damage response [ 10 ], also had variable TF activity across SGS-affected tissues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the data sparsity in snRNA-seq [49], we pseudo-bulked both of our datasets and generated celltype-specific count matrices, as previously described [50]. We converted raw data from the Seurat object counts slot into Single Cell Experiment objects using SingleCellExperiment [47] v1.16.0 while also incorporating necessary metadata with information on sample origin (sample_id), condition (group_id), and cell type (cluster_id).…”
Section: Pseudo-bulking Of Snrna-seq Datamentioning
confidence: 99%